Design guidelines for FRP reinforced concrete structures - Pilakoutas, Kypros; Guadagnini, Maurizio; Neocleous, Kyriacos; Matthys, Stijn (My University, 2011)
This paper presents an outline of the approach proposed by fib task group 9.3 for the next generation of design guidelines for fibre-reinforced polymer (FRP) reinforced concrete structures. The approach covers a range of FRPrelated topics, including material properties, durability, design philosophy, the limit states of bending, shear, cracking and deflection, and bond.
Keywords: Composite structures; Concrete structures; Design methods & aids